A Comparative Study Of Two Heuristic Procedures For Managing Transportation Of The Sample Electric Equipment Company - กิตติปัญญาพัฒน์ รติรัตน์ (Srinakharinwirot University Engineering Journal, 2018)
This research aims to study the vehicle routing problem for a single-warehouse system of the electronic manufacturer. The problem is bounded by vehicle capacity and delivery time-window constraints. Transportation data is collected from the logistic manager and routing experts. To tackle with the problem, we construct two modified heuristic procedures based on the traditional Nearest Neighborhood and Saving Algorithm methods. Our procedures reach the routing solutions that save both distance and total costs. The Modified Saving Procedure produces best performance which saves 18.6% of the total cost comparing to the actual operation of the system. Comparatively, the Modified Nearest Neighborhood Procedure gives the reduction of 13.1% in the total cost. The study shows that the design of heuristic procedures could assist any logistic companies to increase transportation performance, as well as reduce their total cost.